ANALISIS GREEN HALAL TOURISM PADA OBJEK WISATA SETU BABAKAN JAKARTA - Koiriyah Azzahra Zulqah (2023)
Green Halal Tourism combining environmental Sustainability and halal principles has great potential along with the growth of the halal tourism sector. However, the development is not comprehensive, only limited to green tourism without the concept of halal tourism and vice versa. The need for muslim tourists for a tourist destination is not only limited to the uniqueness and tourist attractiveness of the place but also environmentally friendly and guarantees in carrying out worship. The DKI Jakarta government has set pilot destinations for halal tourism and one of them is Setu Babakan. This study aims to analyze the mapping of the green halal tourism and analyze the green halal tourism with the SWOT method. This study uses a descriptive qualitative method with SWOT analysis of primary and secondary data sources in this study. The results of the study show that the Setu Babakan Jakarta tourist attraction is in a growth and build position so that the strategy that must be carried out is growth-oriented to explore new opportunities and improve services.